Capsule-like zeolite catalyst fabricated by solvent-free strategy for para-Xylene formation from CO2 hydrogenation - Gao, Weizhe; Guo, Lisheng; Wu, Qinming; Wang, Chengwei; Guo, Xiaoyu; He, Yingluo; Zhang, Peipei; Yang, Guohui; Liu, Guangbo; Wu, Jinhu; Tsubaki, Noritatsu (Applied catalysis. B, Environmental, 2022)
An efficient Na-FeMn/HZSM-5@Silicalite-1 catalyst was rationally designed for direct conversion of CO2 to aromatics. The tailor-made HZSM-5@Silicalite-1 core-shell zeolite was prepared by a facile solvent-free method. The solvent-free synthesis of core-shell zeolite could not only address pollution issues by eliminating the large utilization of organic reagents, but also exhibit a better performance for separating para-Xylene (PX) from xylenes with the assistance of capsule-like zeolite oriented synthesis. For CO2 to aromatics reaction, Na-FeMn combining with capsule-like HZSM-5@Silicalite-1 catalyst could reach 81.1% PX/X (the C-mol ratio of PX to all xylenes) ratio, which was higher than those of conventional core-shell zeolites, such as HZSM-5@SiO2 and HZSM-5@Silicalite-1 core-shell zeolites which were obtained from traditional chemical liquid deposition and hydrothermal methods. The as-synthesized zeolite paves a new route for efficient conversion of CO2 molecules into valuable PX, and provides a facile method for regulating surface acid properties of zeolite. [Display omitted] •HZSM-5 @Silicalite-1 core-shell zeolite was prepared by a facile solvent-free method.•The external surface acid sites of HZSM-5 zeolite were completely covered by Silicalite-1 shell.•HZSM-5 @Silicalite-1 core-shell zeolite could enhance the PX selectivity in CO2 to aromatics reaction.•HZSM-5 @Silicalite-1 core-shell zeolite exhibited a high PX/X ratio as high as 81.1%.